A multi-strain Synbiotic may reduce viral respiratory infections in asthmatic children: a randomized controlled trial - Ahanchian, Hamid (Electron Physician, 2016)
BACKGROUND AND OBJECTIVE: Asthma is a growing problem worldwide. Acute exacerbations impose considerable morbidity, mortality, and increased cost. Viral respiratory infections are the most common cause (80–85%) of pediatric asthma exacerbations and admissions to the hospital. The aim of this study was to determine the effect of a new synbiotic Lactocare® on viral respiratory infections and asthma exacerbations in asthmatic children. METHODS: In this double blind, placebo-controlled, randomized clinical trial, 72 children with mild persistent asthma, aged between 6 and 12 years, were randomized to receive either Lactocare®, a Synbiotic containing 1 billion CFU/Capsule of Lactobacillus casei, Lactobacillus rhamnosus, Streptococcus thermophilus, Bifidobacterium breve, Lactobacillus acidophilus, Bifidobacterium infantis, Lactobacillus bulgaricus, and Fructooligosacharide (Zist Takhmir, Tehran, Iran) or placebo daily for 60 days. The primary outcome was the number of viral respiratory infections, and secondary outcomes were school absence, salbutamol and prednisolone usage, outpatient visits, and hospital admission for asthma. The outcomes were compared among study groups using the SPSS 11.5 program and the Mann Whitney and Fisher exact tests. RESULTS: Of the 72 children who were enrolled with mild persistent asthma, 36 were assigned randomly to be treated with synbiotic and 36 with placebo. The number of viral respiratory infections was significantly higher in placebo group than the synbiotic group during the first month of intervention (0.74 ± 0.12 vs. 0.44 ± 0.1, p < 0.007) but not during the second month (0.5 ± 0.8 vs. 0.5 ± 0.8, p < 0.641). Considering the total duration of the study (two months), infection episodes also were significantly lower in the synbiotic group (0.92 ± 0.15 vs. 0.69 ± 0.11, p < 0.046). Salbutamol consumption was significantly lower in the synbiotic group, but there were no significant differences in school absenteeism, oral prednisolone use, outpatient visits, or hospital admissions. CONCLUSION: This new synbiotic (a mixture of seven probiotic strains plus fructooligosacharide may reduce episodes of viral infection in asthmatic children. TRIAL REGISTRATION: This study is registered in Iranian Registry of Clinical Trials with registration number of IRCT201509234976N3. FUNDING: This research was supported financially by the Research Council of Mashhad University of Medical Sciences (Grant Number: 911048).